2019
DOI: 10.1109/jsac.2019.2947819
|View full text |Cite
|
Sign up to set email alerts
|

Interference Management and Capacity Analysis for mm-Wave Picocells in Urban Canyons

Abstract: Millimeter (mm) wave picocellular networks are a promising approach for delivering the 1000-fold capacity increase required to keep up with projected demand for wireless data: the available bandwidth is orders of magnitude larger than that in existing cellular systems, and the small carrier wavelength enables the realization of highly directive antenna arrays in compact form factor, thus drastically increasing spatial reuse. In this paper, we carry out an interference analysis for mmwave picocells in an urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…wired Internet networks or wireless cell phone networks) where it acts as a WSN interface. In this section, the proposed FABC‐MACRD protocol's processing steps are laid out [17]. Network‐Assembly, Nearest‐Node‐ Detection, and Consistent‐State are the three primary stages of the FABC‐MACRD protocol's operation (shown in Figure 5).…”
Section: Methodsmentioning
confidence: 99%
“…wired Internet networks or wireless cell phone networks) where it acts as a WSN interface. In this section, the proposed FABC‐MACRD protocol's processing steps are laid out [17]. Network‐Assembly, Nearest‐Node‐ Detection, and Consistent‐State are the three primary stages of the FABC‐MACRD protocol's operation (shown in Figure 5).…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [30] applied a cross-layer approach where interference coordination is applied both at the Physical and MAC (Media Access Control) layers. Beam-forming is used to suppress interference at the physical layer while an optimisation problem is solved at the MAC layer to determine the set of users that will be accommodated by a resource block such that interference is reduced.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the high side lobes outside the cell will not contribute significantly to the intra-cell or inter-cell interference as (i) they will reach the nearby cell through a non-line-of-sight (NLoS) path with a large loss, and (ii) they will lose their strength when they reach the neighboring LoS cells further away. In the literature, it was pointed out that in mm-wave networks the interference stems from the LoS interferers and the NLoS interference is negligible [9]- [12]. Several studies reported between 25-40 dB reduction in the NLoS signal levels as compared to the LoS [13]- [16].…”
Section: Introductionmentioning
confidence: 99%